Anxiety, depression, and quality of life of caregivers of palliative care patients with cancer - Alvarado García, Alejandra María; Vargas-Escobar, Lina María; Arias-Rojas, Mauricio; Avendaño-Vásquez, Carlos Javier; Consuegra-Pareja, Cesar Antonio (Revista Cuidarte, 2025)
Highlights • Caregivers tend to experience symptoms of overburden due to the informal nature of their work and lack of preparation for the physical and emotional challenges of caring for terminally ill patients. • Anxiety and depression in caregivers can negatively impact areas of their lives, such as relationships, socialization, and work performance, especially for those who are employed as caregivers. • Supporting the use of technologies among caregivers is essential to promote care access to information on guidelines for providing care. • Mental health programs led by interdisciplinary teams are relevant to supporting family caregivers of terminally ill patients. Introduction: Palliative care has recently gained importance in the context of life-threatening diseases, such as cancer, that affect the mental health of patients and their caregivers. Psychological symptoms, such as anxiety and depression, are the most prevalent in this population. Objective: To determine the association between anxiety, depression, and quality of life of caregivers of palliative care patients with cancer. Materials and Methods: A quantitative, descriptive, and correlational design was used. A total of 190 primary caregivers recruited from Colombian hospitals and home care programs participated. The Quality of Life in Life-Threatening Illness-Family Carer (QOLLTI-FT) questionnaire, the Beck Depression Inventory-II (BDI-II), and the Beck Anxiety Inventory (BAI) were used. The analysis was performed with SPSS Statistics 26.0, using descriptive and inferential statistics. Results: The predominant sex was female, and the level of education was high school. The mean age of the caregivers was 44.15 years, and the mean age of the patients was 64.51 years. The average time as a caregiver was 33.79 ± 64.77 months. The results show correlations between anxiety and caregiver status (p≤0.000), anxiety and ICT use (p≤0.006). There were also correlations between anxiety, quality of life, and caregiver status (p≤0.000) and between depression and total quality of life (p≤0.001). Discussion: Correlations were also found between depression and quality of life and between hours of daily care and the level of dependency of the cancer patient. This entails the need to manage the psychological symptoms as soon as the family member is diagnosed to prevent alterations in their quality of life that could affect their well-being. Conclusion: Caregivers with moderate or severe depression were more likely to report symptoms of sadness, punishment feelings, self-dislike, suicidal thoughts or wishes, indecisiveness, irritability, changes in appetite, concentration difficulty, and tiredness or fatigue. Among caregivers with mild depression, loss of interest in sex, agitation, and past failure were identified. Strategies for psycho-emotional counseling, education, and support for caregivers are needed. How to cite this article: Alvarado García Alejandra María, Vargas-Escobar Lina María, Arias-Rojas Mauricio, Avendaño-Vásquez Carlos Javier, Consuegra-Pareja Cesar Antonio. Anxiety, depression, and quality of life of caregivers of palliative care patients with cancer. Revista Cuidarte. 2025;16(1):e3670. https://doi.org/10.15649/cuidarte.3670